Counteracting land and soil degradation as a global legal challenge - Goździewicz-Biechońska, Justyna (Przegląd Prawa Rolnego, 2018)
The aim of the article is to identify the problem of land and soil degradation and to recognise the need to counteract these processes as a challenge for the law and policy. The importance of this issue and its connection with the globalisation of food systems (especially the need to consider the interdependencies existing between the aspects of globalisation of food systems and land degradation) has been highlighted and the state of protection of soil and land under international and European Union law described. Given the global effects of land degradation and land scarcity and the fact that regional and local land use decisions are heavily dependent on geographically distant factors, legal instruments to combat land and soil degradation that are local or regional in nature may not be sufficient. Hence the need for action through instruments of international environmental law.